Radioprotective Effects of Kelulut Honey in Zebrafish Model - Mohd Noor Hidayat Adenan; Latifah Saiful Yazan; Annie Christianus; Nur Fariesha Md Hashim; Suzita Mohd Noor; Shuhaimi Shamsudin; Farah Jehan Ahmad Bahri; Khairuddin Abdul Rahim (Molecules, 2021)
Large doses of ionizing radiation can damage human tissues. Therefore, there is a need to investigate the radiation effects as well as identify effective and non-toxic radioprotectors. This study evaluated the radioprotective effects of Kelulut honey (KH) from stingless bee (Trigona sp.) on zebrafish (Danio rerio) embryos. Viable zebrafish embryos at 24 hpf were dechorionated and divided into four groups, namely untreated and non-irradiated, untreated and irradiated, KH pre-treatment and amifostine pre-treatment. The embryos were first treated with KH (8 mg/mL) or amifostine (4 mM) before irradiation at doses of 11 Gy to 20 Gy using gamma ray source, caesium-137 (137Cs). Lethality and abnormality analysis were performed on all of the embryos in the study. Immunohistochemistry assay was also performed using selected proteins, namely γ-H2AX and caspase-3, to investigate DNA damages and incidences of apoptosis. KH was found to reduce coagulation effects at up to 20 Gy in the lethality analysis. The embryos developed combinations of abnormality, namely microphthalmia (M), body curvature and microphthalmia (BM), body curvature with microphthalmia and microcephaly (BMC), microphthalmia and pericardial oedema (MO), pericardial oedema (O), microphthalmia with microcephaly and pericardial oedema (MCO) and all of the abnormalities (AA). There were more abnormalities developed from 24 to 72 h (h) post-irradiation in all groups. At 96 h post-irradiation, KH was identified to reduce body curvature effect in the irradiated embryos (up to 16 Gy). γ-H2AX and caspase-3 intensities in the embryos pre-treated with KH were also found to be lower than the untreated group at gamma irradiation doses of 11 Gy to 20 Gy and 11 Gy to 19 Gy, respectively. KH was proven to increase the survival rate of zebrafish embryos and exhibited protection against organ-specific abnormality. KH was also found to possess cellular protective mechanism by reducing DNA damage and apoptosis proteins expression.